Psychological fundament of reducing of sportsmen’s mistaken actions of fire-applied sport during competition - Краснокутський Микола Іванович (Mykola Krasnokutskyi) (Slobozhanskyi Herald of Science and Sport, 2015)
Purpose: to identify individual psychological characteristics which compensate the impact of psychological determinants of erroneous actions of fire applied sport athletes. Material and Methods: the study involved 102 fire applied sport athletes from the age of 17 to 30. We used the following methods of psycho-diagnosis "Investigation of anxiety" (auth. Ch. D. Spielberg. Adapted version by Y. L. Hanin); test "Proof Test" by B. Bourdon; method "Intellectual liability"; technique "Prediction"; "Tapping test"). Results: the results of research present solving a scientific problem what appears in the disclosure of subjective determinants of erroneous athlete’s actions. Conclusions: the complex of individual psychological characteristics of fire applied sport athletes makes it possible to optimize their training process and reduce the likelihood of errors during the competition.